ISLAM DAN PELESTARIAN LINGKUNGAN HIDUP: Menggagas Pendidikan Islam Berwawasan Lingkungan - Siswanto Siswanto (Institut Agama Islam Negeri Madura)
AbstracFrom theological view, human must be able to appreciate the environment. Religious ethics toward nature takes mankind to be responsible so that they can avoid the damage. In other words, to trash the environments means to destroy the human themselves. On the basis of this context, religious-education institution is expected to prove the graduates with a standard commitment to conserve the ecology . Establishing “Green Madrasah” becomes one of efforts that must be obtained. It is an education model that can transform religious-moral values into each aspect of socio-economic development. This has also been a mode of education which functionalize human as leader, ruler, and maintainer of nature and environmentKata-kata kunciIslam, pendidikan agama, lingkungan hidup, khalifah, madrasah hijau